DISTRIBUTION OF NUTRIENTS IN THE SOUTHERN MARINE REGION OF VIETNAM - Tam, Pham Huu (Vietnam Journal of Marine Science and Technology, 2018)
The paper focused on the investigated results of two surveys in the Northeast monsoon (October 2013) and in the Southwest monsoon (May 2015) of the task of international cooperation in science and technology under the Protocol between Vietnam and the United States (from 2013 to 2015 ), to consider the variation of nutrients in Southern marine region of Vietnam. The data from two above surveys in the Southern marine region of Vietnam showed that in both monsoon periods, the concentrations of nutrients (ammonia, nitrate, phosphate, silicate) were distributed in coastal stations and near the Mekong estuaries), most of the concentrations of the nutrients (nitrate, phosphate, silicate) were distributed on the top layer of waters (5 meters of water layer). In South Central marine area (high upwelling region), the concentrations of nutrients (nitrate, phosphate) were concentrated in coastal stations and on the top layer of waters in both monsoon periods. In estuaries of the Mekong, the concentrations of nutrients (nitrate and silicate) in the Northeast monsoon were usually higher than those in the Southwest monsoon in coastal stations. The molecular ratios (N/P) showed that phosphorus (P) always played a role as a limiting nutrient in area of the Mekong, meanwhile in the South Central marine area there was an opposite trend.